2015
DOI: 10.1080/14786419.2015.1020490
|View full text |Cite
|
Sign up to set email alerts
|

Naringenin and quercetin – potential anti-HCV agents for NS2 protease targets

Abstract: Nonstructural proteins of hepatitis C virus had drawn much attention for the scientific fraternity in drug discovery due to its important role in the disease. 3D structure of the protein was predicted using molecular modelling protocol. Docking studies of 10 medicinal plant compounds and three drugs available in the market (control) with NS2 protease were employed by using rigid docking approach of AutoDock 4.2. Among the molecules tested for docking study, naringenin and quercetin revealed minimum binding ene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
26
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 9 publications
1
26
0
Order By: Relevance
“…NS2 is a transmembrane protein of 21-23 kDa that is not required for RNA replication but that is vital to produce infectious viruses in vitro , and it acts as an apoptosis inhibitor[ 191 , 209 ]. Using a docking analysis, it has been identified that naringenin could be an NS2 protease inhibitor.…”
Section: Antiviral Properties Of Naringeninmentioning
confidence: 99%
“…NS2 is a transmembrane protein of 21-23 kDa that is not required for RNA replication but that is vital to produce infectious viruses in vitro , and it acts as an apoptosis inhibitor[ 191 , 209 ]. Using a docking analysis, it has been identified that naringenin could be an NS2 protease inhibitor.…”
Section: Antiviral Properties Of Naringeninmentioning
confidence: 99%
“…An additional anti-HCV activity by quercetin-based treatment was recently suggested [ 101 ]. Lulu et al predicted the 3D structure HCV NS2 protein and performed docking studies to identify phytochemical compounds which could have strong affinity towards its protease.…”
Section: Plant-derived Compounds With Anti-hcv Propertiesmentioning
confidence: 99%
“…Naringenin was also co-incubated with WY14643 and no increased effect was observed, demonstrating the possible effect of naringenin in PPARα activation. More recently, Lulu et al analysed by molecular docking studies the structural interactions between naringenin and the protein NS2 protease [ 101 ]. They demonstrated that naringenin exhibited a lower minimum binding energy (− 7.97 kcal/mol) than RBV (− 5.89 kcal/mol) to bind to NS2 protein, suggesting that naringenin requests a lesser amount of energy to disrupt HCV NS2 protein.…”
Section: Plant-derived Compounds With Anti-hcv Propertiesmentioning
confidence: 99%
“…Recent studies on C. intybus have found some of the important constituents such as caffeic acid derivatives, phenylacetic acid esters, fructooligosaccharides, flavonoids, coumarins, polyphenol, cichoriosides, sonchuside A, ixerisosides, magnolialide, eudesmanolides, bitter sesquiterpene lactones, inulin, and vitamins (El-Lakany et al 2004; Hussain et al 2011; Kumari, Ali, & Aeri 2012; Kirillov et al 2017; Lulu et al 2016). In this paper, we report the isolation and characterization of one new 28 β -hydroxytaraxasterol besides six known compounds from the aerial parts of C. intybus .…”
Section: Introductionmentioning
confidence: 99%